Amphiphilic electrospun fibres of poly(methacrylic acid)-graft-poly(dimethylsiloxane) copolymers as a means to controlling electrospun fibre morphology and obtaining nanofibre hydrogels - Meltz, Freda-Jean (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.